KLASIFIKASI SATUAN LINGUAL LEKSIKON KERAMIK DI DESA SAKOK, KELURAHAN SEDAU, KOTA SINGKAWANG - Kusuma Putri, Indrie Sari; Heryana, Nanang; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of the ceramic lexicon research is to find out the form, lexical meaning, cultural meaning, and supplement of the Indonesian language learning text material for the 2013 curriculum. The method used in this research is descriptive method and uses an ethnolinguistic approach. The source of the data under study is the speech from the informant containing the ceramic lexicon found in Singkawang City in the form of words and phrases. The technique used in this study, namely, see, record and record. Data collection tools in the form of recorders and stationery. Based on the research conducted, the data collected was fifty-three ceramic lexicons in Singkawang City. Lexicon ceramics in Singkawang City in this study consisted of three forms namely monomorphemic and polymorphemic words and phrases. The lingual unit in the form of monomorphemism is twelve words. The lingual unit in the form of eleven word polymorphisms. The lingual unit in the form of phrases amounted to thirty phrases. Material based lexicon researchers found as many as nine lexicons. The tool-based lexicon researchers found fourteen lexicons. The lexicon is based on the researcher, finding as many as one lexicon. The process-based lexicon finds as many as twelve lexicons. While the lexicon based on the product researchers found as many as seventeen lexicons.Â Keywords: Lexicon, Chinese Ceramics, Lingual Unit, Singkawang